2016
DOI: 10.1145/3003977.3004000
|View full text |Cite
|
Sign up to set email alerts
|

Aurora

Abstract: Public lighting accounts for a considerable amount of the total electricity consumption. Solutions to reduce its energy (and cost) footprint do exists, and they often translate into costly lamp replacement projects, which cannot be afforded by the majority of municipalities. To solve this situation, we propose Aurora: a low-budget, easy-to-deploy IoT control system that exploits the ubiquity of cellular networks (2- 4G) and scalable Cloud computing architectures to allow Smart Cities to save on the public ligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Smart homes can significantly increase the comfort of living and improve user safety through features such as remote control of parameters (e.g., temperature, light intensity), device management and control, presence detection or simulation, and identi- Transport (Bhatti et al, 2019;Gandhi, 2016;Ji et al, 2014;Masek et al, 2016;Rizwan et al, 2016;Sadhukhan, 2017) Waste management (Ali et al, 2020;Anagnostopoulos et al, 2017;Bharadwaj et al, 2016;M. Sharma et al, 2020) Environmental monitoring and protection (Duangsuwan et al, 2018;Indhumathi & Dineshkumar, 2019;Malche et al, 2019;Shah & Mishra, 2016) Homes (Dutta & Roy, 2017;Dwivedi et al, 2021;Hui et al, 2017) Healthcare (Abril-Jiménez et al, 2020;Bryant et al, 2017;Dawood & Sah, 2021;Poongodi et al, 2021) Disaster prevention (Loftis et al, 2018;Sakhardande et al, 2016; Lightning (Rossi et al, 2016;Sikder et al, 2018Sikder et al, , 2018Tambare et al, 2016;Xu & Wang, 2020) 2…”
Section: Engineering Management In Production and Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Smart homes can significantly increase the comfort of living and improve user safety through features such as remote control of parameters (e.g., temperature, light intensity), device management and control, presence detection or simulation, and identi- Transport (Bhatti et al, 2019;Gandhi, 2016;Ji et al, 2014;Masek et al, 2016;Rizwan et al, 2016;Sadhukhan, 2017) Waste management (Ali et al, 2020;Anagnostopoulos et al, 2017;Bharadwaj et al, 2016;M. Sharma et al, 2020) Environmental monitoring and protection (Duangsuwan et al, 2018;Indhumathi & Dineshkumar, 2019;Malche et al, 2019;Shah & Mishra, 2016) Homes (Dutta & Roy, 2017;Dwivedi et al, 2021;Hui et al, 2017) Healthcare (Abril-Jiménez et al, 2020;Bryant et al, 2017;Dawood & Sah, 2021;Poongodi et al, 2021) Disaster prevention (Loftis et al, 2018;Sakhardande et al, 2016; Lightning (Rossi et al, 2016;Sikder et al, 2018Sikder et al, , 2018Tambare et al, 2016;Xu & Wang, 2020) 2…”
Section: Engineering Management In Production and Servicesmentioning
confidence: 99%
“…IoT solutions ensure remote control of lighting installations, signalling irregularities and real-time monitoring of electricity consumption. Smart lighting systems increase the efficiency of the lighting management process, enable cities to reduce their electricity expenses, and improve the safety of residents (Rossi et al, 2016;Sikder et al, 2018;Tambare et al, 2016). An example is the self-cleaning urban streetlight system proposed by Xu and Wang (2020).…”
Section: Security and Privacymentioning
confidence: 99%
“…In the past decades, a growing number of municipalities have been joining the trend of turning their cities into "smart cities". One dimension of this smart city phenomenon is the street lighting system (e.g., Jennison, Clifford, Horency, Black, & Ng Zheng, 2017;Rossi, Gaetani, & Defina, 2016). Based on the understanding that knowledge presents a powerful economic advantage (Nowik & Zamir, 2003) the methodology for improving the system's power usage usually begin with mapping the entire city system (Beccali, Bonomolo, Ciulla, Galatioto, & Brano, 2015).…”
Section: Smart Cities and Digital Literacymentioning
confidence: 99%
“…For instance, Leccisi et al [ 11 ] showed a platform to collect, handle, organize, and evaluate the dynamic and static strategic data of urban energy-intensive infrastructure (public lighting, public buildings, e.g., schools), to provide a constant and dynamic assessment of their functional and energetic performances. Rossi et al [ 12 ] proposed a low-cost IoT public lighting control system to exploit cellular networks and cloud computing architectures. Moreover, IoT-based intelligent lamppost systems have been developed to provide smart infrastructure, communicating environmental parameters and images to IoT servers [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%